2013
DOI: 10.1080/01494929.2013.766296
|View full text |Cite
|
Sign up to set email alerts
|

Couples, Money, and Expectations: Negotiating Financial Management Roles to Increase Relationship Satisfaction

Abstract: How couples handle money has become a popular subject among scholars, practitioners, and the popular press. However, little is known about how finances should be treated within a clinical context. This study examined the financial management roles in which couples participate and their satisfaction level with these roles as well as couples' communication tactics surrounding money and their impact on relationship and financial satisfaction. Results suggested that having shared goals and values about money were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 35 publications
3
59
1
7
Order By: Relevance
“…If so, then engaged couples may be happier because they focused on one goal (i.e., planning the wedding) and put aside concerns about future financial arrangements. However, Archuleta (2013) found that individuals who shared the same views as their partner about financial management roles, goals, and values reported higher relationship satisfaction. In a follow-up study using the same sample, Archuleta and colleagues (2013) examined the mediating effect that shared goals and values have on the association between financial satisfaction and relationship satisfaction.…”
Section: Shared Financial Valuesmentioning
confidence: 67%
See 3 more Smart Citations
“…If so, then engaged couples may be happier because they focused on one goal (i.e., planning the wedding) and put aside concerns about future financial arrangements. However, Archuleta (2013) found that individuals who shared the same views as their partner about financial management roles, goals, and values reported higher relationship satisfaction. In a follow-up study using the same sample, Archuleta and colleagues (2013) examined the mediating effect that shared goals and values have on the association between financial satisfaction and relationship satisfaction.…”
Section: Shared Financial Valuesmentioning
confidence: 67%
“…Because shared views about financial values have been associated with higher relationship satisfaction (Archuleta, 2013), we further hypothesized that perceived financial mutuality would be directly and positively associated with relationship satisfaction (Hypothesis 2). Finally, we tested for the mediating effect of perceived financial mutuality on the association between the personal components of the comparison level (participant's financial management quality and perceived partner's financial behavior) and relationship satisfaction (Sabatelli & Shehan, 2004) …”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…An understanding of partners' perceived roles in the relationship in the presence of changing income dynamics is necessary, especially concerning female breadwinners' perceptions of individual versus partnered financial management responsibilities. Archuleta (2013) suggested that when partners take on financial management roles that they enjoy, they are more likely to be satisfied in their relationships.…”
Section: Discussionmentioning
confidence: 99%